2017
DOI: 10.3390/ijerph14091031
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Survival Sex and Borderline Personality Disorder Symptoms in a High Risk Female Population

Abstract: Engaging in survival sex and mental illness are overrepresented within homeless populations. This article assesses the relationship between symptoms of borderline personality disorder (BPD) and engaging in survival sex among homeless women. One hundred and fifty-eight homeless women completed surveys on self-reported BPD symptomology and sexual history. Bivariate and multivariate analyses conducted in this study provided insights into the association of experiencing BPD symptoms and engaging in survival sex. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Engaging in survival sex is over-represented within homeless populations ( 52 ), and data show robust associations with symptoms of borderline PD, childhood abuse, and post-traumatic stress disorder among homeless women ( 52 , 53 ), suggesting that older individuals with high levels of impulsivity symptoms may be especially at risk ( 52 ). Similar approaches among homeless men have shown that risky sexual behavior is accompanied by common symptoms of PD’s and predicts treatment outcomes and suboptimal achievements in health-promoting or prosocial behaviors ( 54 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Engaging in survival sex is over-represented within homeless populations ( 52 ), and data show robust associations with symptoms of borderline PD, childhood abuse, and post-traumatic stress disorder among homeless women ( 52 , 53 ), suggesting that older individuals with high levels of impulsivity symptoms may be especially at risk ( 52 ). Similar approaches among homeless men have shown that risky sexual behavior is accompanied by common symptoms of PD’s and predicts treatment outcomes and suboptimal achievements in health-promoting or prosocial behaviors ( 54 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Homeless or runaway women, sexual minorities, and minors are more likely to report engaging in survival sex. In a sample of homeless women, the lifetime prevalence of survival sex was 23.8% (Ivanich et al, 2017). Similarly, Oppong and colleagues found 51% of homeless youth reported survival sex (2016).…”
Section: Survival Sex and Healthmentioning
confidence: 99%
“…In the former, otherwise treatable maladies can remain unaddressed, multiplying eventual treatment costs when cases are discovered at more advanced stages. Such is the situation, for example, with mental illness among homeless and street dwelling populations [ 4 6 ]. An embedded “hidden” population can also frustrate intervention efforts that might otherwise be effective in the ambient population, preventing control of infection prevalence [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the former, treatable maladies can remain out of reach, multiplying eventual treatment costs when cases are discovered only in their most severe form. Such is the situation, for example, with mental illness among homeless and street dwelling populations [BFB09,Bur95,IWLD17]. In other situations, the "hidden" nature of the population may frustrate intervention efforts that are effective in the ambient population, preventing control of infections despite well-known contagion dynamics [PWR + 93].…”
mentioning
confidence: 99%